Brincando no maracatu pimpões e biluca: saberes, memórias e ancestralidade na construção da cultura afrodescendente - Silva Neto, Euclides Flor da (Universidade Federal Rural do Semi-Árido, 2018)
Socio-cultural analysis of the street carnival as a re-signification of the knowledge, memories and ancestry in the construction of Afrodescendant culture in Mossoró-RN. Inserted in the life story of the narrator-researcher as a popular player of the street carnivals, he seeks to recover and analyze the narratives around the maracatus, as places full of attachments and affections, smells, smells, colors, shapes and textures that create feelings of belongings where the ancestry dwells and the preservation of traditional knowledge. It presents Maracatu as a symbolic place and with a strong affective load with its formative and resistance processes of Afro-Brazilian culture. It allows to bring other voices that make up the maracatu, expressing the vibrations, sensations, rituals and symbols present in the understanding of the dynamics crossed by the processions, constructed in the individual and collective experiences, in the unfolding of its multiple meanings. In a qualitative way, the narrative is developed through the (auto) biographical narrative analysis method, retrieving the oral histories of two important subjects of the Mossoró / RN carnival, Cristina Gomes Paulista - known as "Cristina dos Pimpões", and Francisca Maria de Souza - "Dona Biluca". These narratives are analyzed in the light of the re - signification of ancestry and the pedagogical formation that takes place outside the school in search of the construction of citizenship and subjectivity as parameters of the Afro - descendant identity of Maracatu. It recreates the memory of local manifestations involving maracatu as a learning space in which ideas, meanings and senses that dialogue with the body, art and education circulate.
Monografia
Keywords: Maracatu; Narrativa autobiográfica; Ancestralidade; Memórias; Saberes; Biluca; Pimpões; Maracatu; Autobiographical narrative; Ancestry; Memoirs; You know; Biluca; Pimpões; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO RURAL